Diseño de un sistema contable para la asociación artesanal san francisco de Toacoaso, año 2018. - Iza Alomoto, Sandra Maritza (2018)
The San Francisco de Toacaso Artisan Association, due to its recent creation, does not have an accounting system, which prevented them from carrying out their activities efficiently, causing misinformation on the part of the people who manage the association and ignorance of the results obtained, the objective of this integrating project was to design an accounting system that facilitated the timely registration of its financial transactions, creating a model that contributed to organizational strengthening, allowing competitive advantages to be obtained and, most importantly, avoiding the inadequate management of its resources, since The development of the San Francisco de Toacaso Artisan Association depends on this. In order to obtain real information, research methods have been used, such as bibliographic and documentary compilation, techniques such as the survey, and observation guides for managers and members of the San Francisco de Toacaso Artisan Association, with the objective of gathering information for the execution of the project, to achieve the above, the situational diagnosis of the collection center was carried out, which provided a clearer idea of the problem in question, through which the realization of the project is justified. The competences related to the professional field and the scientific and technical foundation were described, the same ones that helped in the accomplishment of the work. Then, information was collected from the people who manage the Association through surveys and interviews of the different processes that are developed, with which the proposal for the formulation of an accounting system was interpreted and put forward. To finalize the proposal was developed to solve the problem found in the organization, which seeks to improve procedures and controls through the design of an accounting system, so that your information is reliable and can make more accurate decisions.